Coupled Thermo-Hydro-Mechanical-Chemical Processes in Fractured Rocks Fundamentals, Modeling and Applications - Zhao, Zhihong (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents the coupled Thermo-Hydro-Mechanical-Chemical (THMC) processes in fractured rocks at varying scales from single fractures to fracture networks. It also discussed the implication and potential application of the advanced understanding of coupled THMC processes in fractured rocks for geotechnical and geo-energy engineering.
Chapter 1 Introduction -- Part 1 Fundamentals -- Chapter 2 Shear behavior and damage characteristics of rock fracture -- Chapter 3 Water-rock interaction in rock fracture -- Chapter 4 Thermal effects on rock mechanical and hydraulic behaviors -- Part 2 Numerical methods -- Chapter 5 Governing equations for coupled THMC processes in fractured rocks -- Chapter 6 Numerical Modeling on coupled THMC processes in fractured rocks -- Chapter 7 Equivalent flow channels in fractured rocks.
Keywords: Geotechnical engineering; Engineering geology; Refuse and refuse disposal; Geotechnical Engineering and Applied Earth Sciences; Geoengineering; Waste Management/Waste Technology